2x – y = 5
Put into slope intercept form
y = 2x - 5
So the slope = 2
For a line to be perpendicular the product of the slopes of the two lines must equal -1
Therefor the slope must be -1/2
The perpendicular line in slope intercept form
y = -1/2x + b
Since the line passes through point (3, 0)
0 = -1/2(3) + b
0 = -3/2 +b
b = 3/2
Equation of perpendicular line
y = -1/2x +3/2
Put into slope intercept form
y = 2x - 5
So the slope = 2
For a line to be perpendicular the product of the slopes of the two lines must equal -1
Therefor the slope must be -1/2
The perpendicular line in slope intercept form
y = -1/2x + b
Since the line passes through point (3, 0)
0 = -1/2(3) + b
0 = -3/2 +b
b = 3/2
Equation of perpendicular line
y = -1/2x +3/2
-
Write the equation in y intercept form :
2x – y = 5 =>
y = 2x - 5
If the slope of this line is 2, then the slope of a line that is perpendicular to it is -(1/2)
Now begin writing the equation for this new line
y = mx + b =>
y = -(1/2)x + b
Then they tell us that it must pass through (3,0), so plug these values in to find b:
y = -(1/2)x + b =>
0 = -(1/2)*3 + b =>
b = 3/2
Now you have the equation you're looking for:
y = -(1/2)x + (3/2)
2x – y = 5 =>
y = 2x - 5
If the slope of this line is 2, then the slope of a line that is perpendicular to it is -(1/2)
Now begin writing the equation for this new line
y = mx + b =>
y = -(1/2)x + b
Then they tell us that it must pass through (3,0), so plug these values in to find b:
y = -(1/2)x + b =>
0 = -(1/2)*3 + b =>
b = 3/2
Now you have the equation you're looking for:
y = -(1/2)x + (3/2)
-
y = - x/2 + 3/2